Staphylococci and mammaliicocci: Which species are important for udder health on organic dairy farms? - C.E. Jeffrey; P.R.F. Adkins; S. Dufour; J.W. Barlow (Journal of Dairy Science)
ABSTRACT: Variation in species distribution and diversity of staphylococci and mammaliicocci (SaM) causing intramammary infections in dairy cattle is associated with different management practices. Disparate selective pressures on organic dairies could potentially result in population differences of these mastitis-causing bacteria. The species-specific effect on quarter SCC of SaM for a population of certified organic dairies has not been described previously. The current study presents data from a longitudinal study of 10 certified organic dairy farms. The objective was to estimate how quarter milk somatic cell count (qmSCC) varied as a result of infection with the most frequently isolated SaM species. Aerobic culture of quarter milk samples to identify IMI was conducted in parallel with determination of qmSCC. A linear hierarchical repeated measures mixed model was used to estimate qmSCC for quarters with an IMI caused by a given SaM species, compared with culture-negative quarters. The model included DIM at time of sampling to adjust qmSCC estimates for each SaM species. The final dataset consisted of 648 quarters with an IMI due to 10 different SaM species and 1,972 culture-negative quarters. Staphylococcus chromogenes was the most frequent species, followed by S. aureus, S. haemolyticus, and S. simulans. A large amount of variability was observed in the SCS for culture-negative quarters and those infected with many SaM species, especially S. chromogenes, S. haemolyticus, S. simulans, and S. aureus. Somatic cell score was significantly higher in quarters infected with S. agnetis, S. aureus, S. chromogenes, S. devriesei, S. haemolyticus, S. hyicus, S. simulans, S. warneri, and S. xylosus compared with culture-negative quarters. The highest cell count was for quarters infected with S. warneri, followed by S. aureus, S. agnetis, and S. hyicus. The relative distribution of various SaM species and their effect on qmSCC in this population of small to midsize organic farms was similar to previous studies. Although the increase in qmSCC was modest for most SaM species observed, the widespread prevalence of these intramammary pathogens could potentially contribute to sizable increases in bulk tank SCC.